Perkembangan Akuntansi Akrual pada Sektor Publik: Analisis Bibliometrik - Pratama, Hamdan Adhymaz; Mutmainah, Siti (Direktorat Sistem Perbendaharaan, 2025)
This study aims to analyze the development of scientific publication data on the theme of accrual accounting in the public sector from the Scopus database. The results of this study can be utilized for mapping the writing of additional articles on similar topics based on title, abstract and keyword analysis. The approach, utilising bibliometric analysis with the Biblioshiny application, was employed to analyse 262 articles collected from 97 journals spanning the period from 2005 to 2023. Journals with high impact and the most productive authors on this topic were identified. Based on the analysis results, the Public Money and Management Journal (Q2) publishes the most articles on this theme. Irvine Lapsley's article is one of the most influential publications, with a total of 161 citations. The dominant research areas include accrual accounting management, accounting policy implementation and its impact on transparency and accountability. Recommendations for further research include a more in-depth exploration of the impact of accrual accounting on the efficiency of public sector financial management and a comparative analysis of public accounting policies.